Q the autobiography of Quincy Jones - Jones, Quincy 1933-2024 (Harlem Moon / Broadway Books, 2002)
"Quincy Jones has led one of the most musically influential American lives of this century. In Q, he fainally tellsit all, beginning with his rough-and -tumble childhood on Chicago's South Side; through his teenage years in Seattle, when he took up the trumpet and was literally saved by music; and into his life as a musician, playing backup for Billie Holiday and touring the world with the Lionel Hampton Band
Keywords: Jones, Quincy -- 1933-2024; Jones, Quincy / 1933-; Jazz musicians / United States / Biography; Musiciens de jazz / États-Unis / Biographies; Jones, Quincy / 1933- / https://id.oclc.org/worldcat/entity/E39PBJxMrcpRbVFDW8b7VgKPQq; Jazz musicians; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Biographies; Autobiografie